Quadrivalent cell culture influenza virus vaccine. Comparison to egg-derived vaccine - Alberto Pérez-Rubio; Julio Ancochea; Jose María Eiros Bouza (Taylor & Francis Group, 2020)
Influenza virus infections pose a serious public health problem and vaccination is the most effective public health intervention against them. The current manufacture of influenza vaccines in embryonated chicken eggs entails significant limitations. These limitations have been overcome by producing vaccines in cell culture, which allow a faster and more flexible response to potential pandemic threats. Given the impact of influenza B virus on disease burden, the availability of quadrivalent vaccines is useful for increasing the rate of protection from disease. This paper analyzes the limitations of the current production of influenza vaccine in eggs and the advantages of vaccines developed in cell culture, as well as their safety, tolerability, efficacy and effectiveness. Additionally, we reflect on the contribution of new quadrivalent vaccines from cell culture as an alternative in seasonal vaccination campaigns against influenza.